Relationship between physical activity practice and metabolic profile of postmenopausal women under treatment with aromatase inhibitors for breast cancer. (September 2017) - de Paulo, Thais R.S.; Viezel, Juliana; Aro, Bruna L.; Seidinger, Sylvia C.; Trindade, Ana Carolina A.C.; Christofaro, Diego G.D.; Freitas, Ismael F.
Abstract: Objective: To analyze the relationship between physical activity practice and metabolic profile of postmenopausal women under treatment with aromatase inhibitors (AIs) for the treatment of breast cancer. Study design: Cross-sectional study, conducted with 101 postmenopausal women (aged 50–80 years). The sample was divided into two groups; group without cancer (GW; n = 65) and breast cancer group treated with AIs (GC; n = 36). Physical activity (PA) was evaluated by questionnaire. Correlations between physical activity and metabolic variables were made by Pearson's correlation coefficient and the magnitude of these relationships by linear regression. Results: In GW, there were observed significant inverse correlations between physical activity and VLDL cholesterol (β = −0.036; 95% CI = −0.068; −0.004); triglycerides (β = −0.036; 95% CI = −0.015; −0.002); glycose (β = −0.029; 95% CI = −0.047; −0.012); and C-reactive protein (β = −0.44; 95% CI = −0.085; −0.003). However, for women under treatment of AIs there was no relationship between physical activity and metabolic variables. Conclusion: The amount of physical activity practice is inversely related to lipid profile, glucose and C-reactive protein in women without breast cancer. This relation was not observed in the cancer survivors, suggesting that the use of aromatase inhibitors could influence or low intensity of physical activity.